SHAŃARAQ KONCEPTI QARAQALPAQ NAQÍL-MAQALLARÍ MÍSALÍNDA - Berdimuratova, G.A. (SCIENCE and SOCIETY, 2024)
In this article, the understanding of the concept associated with the concept of “family” in the Karakalpak language is explored by comparing it with various terms used in the language based on the culture of the Karakalpak population. According to the anthropocentric approach, it is clear that the main factor of language is man. The place of man in the environment, the terms used in Karakalpak families, were determined on the basis of scientific sources. The concept of “family” was studied in more detail, explanatory words of the Karakalpak language, proverbs, and ethnographic materials were used more. Thus, the words associated with the concept of “family” were fully understood.